Shared Governance among Nurses: A Descriptive Study from Jordan - Zaid Al-hamdan; Tareq Abu- Erjeh; Hala Bawadi; Muayyad Ahmad; Mohammad Alhamdan (Jordan University of Science and Technology, 2022)
Background: Shared governance (SG) of employees is crucial in building trust within healthcare organizations. Control over practice, ownership of actions, the feeling of independence, and involvement in work decisions significantly increases employees’ intent to stay, whereas exclusion from the decision-making process leads to a higher rate of turnover. Improve decision-making and enhance collaboration among the nursing staff and nurse leaders; pave the way for greater autonomy and management of healthcare delivery. Purpose: To examine the SG perceptions among Jordanian registered nurses in different clinical areas. Methods: A descriptive, cross-sectional design was used. A convenience sample of 261 nurses was recruited from three hospitals in Jordan between 2017 and 2018. tool Results: The total SG score ranged between 86 and 344 with a mean of 175.6. There was a slight difference in total SG scores among hospitals. However, when the subscales were compared across the three hospitals, some differences emerged specifically in nurses’ total perceived personnel and total perceived goal and conflict. The median age of the sample was 28 years, and about half of them (54%) were males. Conclusion: Our results demonstrated that there is room to increase the level of nurses’ control and influence in decision-making, particularly in those departments that scored lower on the IPNG    Implications: The study results have implications for nursing administration, policy development, and decision-making when choosing/adopting a model of organizational SG to cultivate excellence in the workplace. Key Words: Shared Governance; Registered nurses; Work environment